2022
DOI: 10.1016/j.heliyon.2021.e08600
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring mechanical properties and degradation rate of maxillofacial implant based on sago starch/polylactid acid blend

Abstract: Tailoring mechanical properties and degradation rate of maxillofacial implant based on Sago Starch/Polylactid Acid Blend, HELIYON, https://doi.org/10.1016/j.heliyon.2021.e08600. This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 85 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…This results in a change in the geometry of the biocomposite material. In addition, the greater the water absorption in the biocomposite material, the poorer the interface bond strength of the matrix and reinforcement, so the mechanical properties decrease [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…This results in a change in the geometry of the biocomposite material. In addition, the greater the water absorption in the biocomposite material, the poorer the interface bond strength of the matrix and reinforcement, so the mechanical properties decrease [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2022) [27]. It is revealed that the incorporation of PEG exhibited a plasticization effect in case of the polymer blends of polylactic acid (PLA) and starch.…”
Section: In Uence Of Peg Contents On the Properties Of Tps/nrmentioning
confidence: 99%
“…Moreover, the effect of polyethylene glycol (PEG) content was also investigated as it has been reported that PEG can act as a processing aid and effectively improves the ductile properties of materials [25][26][27].…”
Section: Introductionmentioning
confidence: 99%